2015
DOI: 10.3390/su7054952
|View full text |Cite
|
Sign up to set email alerts
|

Game Analysis and Simulation of the River Basin Sustainable Development Strategy Integrating Water Emission Trading

Abstract: Water emission trading (WET) is promising in sustainable development strategy. However, low participation impedes its development. We develop an evolutionary game model of two enterprise populations' dynamics and stability in the decision-making behavior process. Due to the different perceived value of certain permits, enterprises choose strategy (bidding for permit) or strategy (not bidding). External factors are simplified according to three categories: -bidding related cost, -price and -penalty. Participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For example, Kim [22] and Sice et al [23] use SD to simulate the dynamic and complex evolutionary process of the hybrid strategy game model and duopoly game model. Liu et al [24] simulate an evolutionary game model of two enterprise populations' dynamics and stability in the decision-making behavior process. It can be seen that SD provides an effective aid for studying the complex dynamic process of evolutionary games under incomplete information conditions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Kim [22] and Sice et al [23] use SD to simulate the dynamic and complex evolutionary process of the hybrid strategy game model and duopoly game model. Liu et al [24] simulate an evolutionary game model of two enterprise populations' dynamics and stability in the decision-making behavior process. It can be seen that SD provides an effective aid for studying the complex dynamic process of evolutionary games under incomplete information conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Evolutionary game theory is an application of the mathematical framework of game theory to the dynamics of animal conflicts (including, of course, the conflicts in which people engaged) [32,33]. Following the development of evolutionary game theory, it has been widely used to analyse industrial transfer [34,35], pollution control [36][37][38][39][40][41], and policy-making [41][42][43].…”
Section: Evolutionary Game Modelmentioning
confidence: 99%
“…The academic community has applied the evolutionary game model to environmental protection research and made great progress. For example, Liu et al (2015) developed an evolutionary game model of two enterprise populations' dynamics and stability for decision-making. By building a system dynamics model, they simulated the aforementioned game and found that the initial choice of strategy was essential to the final result.…”
Section: Introductionmentioning
confidence: 99%
“…By building a system dynamics model, they simulated the aforementioned game and found that the initial choice of strategy was essential to the final result. They concluded that it is important to check the saddle point and external factors [28]. Zhao et al (2016) established an evolutionary game model to investigate the responses of enterprises to carbon-reduction policies.…”
Section: Introductionmentioning
confidence: 99%